Modified tunicate nanocellulose liquid crystalline fiber as closed loop for recycling platinum-group metals. (15th January 2020) - Hong, Hye-Jin; Yu, Hayoung; Hong, Seungki; Hwang, Jun Yeon; Kim, Seung Min; Park, Min Sang; Jeong, Hyeon Su
Graphical abstract: Highlights: Direct use of recovered platinum group metals (PGMs) from waste is demonstrated. Tunicate nanocellulose fibril liquid crystal(TCNF LC) fiber is used for biosorption. TCNF LC fiber has high mechanical strength and flexibility with open-cell structure. Polyethylenimine modified TCNF LC fiber shows high PGM uptake in waste effluent. The PGMs adsorbed on TCNF LC fiber forms nanoclusters for high catalytic activity. Abstract: Rising demand and elemental rarity requires the recycling of precious metals such as platinum group elements (PGMs). Recently, biosorption has been focused on the capability of recovering precious metals, but in practice, recycling is inefficient or far away from a closed-loop material system. Here we use a polyethylenimine (PEI)-grafted spun-fiber made of cellulose nanofibril (CNF) extracted from a tunicate as a biosorbent for PGMs. Liquid crystallinity (LC) of TCNF suspension appears to contribute the generation of well-developed open porous structure in the fiber. We show the fiber has the selectivity and high capacity of Pt (120.2 mg/g, 86%) and Pd (26.5 mg/g, 74.2%) adsorption under the presence of other metals in simulated automobile waste. The adsorbed Pt and Pd with nano-scale clusters were uniformly distributed on the porous surface, which were directly applied as a catalyst. These results propose an easy approach to recover precious metals and reuse them directly, thereby closing loops of metal recycling.